Reduced cross-border lending and financing costs of SMEs - Franziska Bremus; Katja Neugebauer (Journal of International Money and Finance, 2018)
This paper investigates how the withdrawal of banks from their cross-border business impacted the borrowing costs of European firms since the crisis. We combine aggregate information on total and cross-border credit with firm-level survey data for the period 2010–2014. We find that the decline in cross-border lending led to a deterioration in the borrowing conditions of small firms. In countries with more pronounced reductions in cross-border credit inflows, the likelihood of a rise in firms' external financing costs increased. This result is mainly driven by the interbank channel, which plays a crucial role in transmitting shocks to the real sector across borders.
Keywords: F34; F36; G15; G21; 330; International banking; Credit constraints; Firm finance